Making strategy : - Eden, Colin (Sage Publications, 1998)
It provides a much needed guide to the strategy-making process by: elaborating the key concepts and theories of strategic management; illustrating through case vignettes the issues inherent in the process of strategy making; and providing extensive and detailed practical guidelines on the methods, techniques and tools employed in the case vignettes.